PARTISIPASI MASYARAKAT DALAM PENGENDALIAN KEBAKARAN LAHAN GAMBUT DI DESA MUARA MEDAK KECAMATAN BAYUNG LENCIR KABUPATEN MUSI BANYUASIN PROVINSI SEMATERA SELATAN - Wardoyo, Wardoyo; Yuningsih, Lulu; Kurniawan, Rahmat (Universitas Muhammadiyah Palembang, 2017)
Community Participation in Peatland Fire Control in Muara Medak Village, Bayung Lencir Subdistrict, Musi Banyuasin Regency, Sumatera Selatan Province. This research aims to determine how much the level of community participation in responding to peatland fire control that often occurs when the dry season comes. This research was conducted in Muara Medak Village, Bayung Lencir Subdistrict, Musi Banyuasin Regency of Sumatera Selatan Province from March to August 2016. The method used research is the purposive sampling by taking sample 10%. Based on the results obtained in this research that some people in Muara Medak Village have participated in the peatland fire control, it is seen from the meeting of the interest the people who do land processing still take into account in order to avoid the spread of land fires during the land clearing.